Regulation of leptin receptor‐expressing neurons in the brainstem by TRPV1. Issue 9 (September 2014) - Zsombok, Andrea; Jiang, Yanyan; Gao, Hong; Anwar, Imran J.; Rezai‐Zadeh, Kavon; Enix, Courtney L.; Münzberg, Heike; Derbenev, Andrei V.
Abstract The central nervous system plays a critical role in the regulation of feeding behavior and whole‐body metabolism via controlling the autonomic output to the visceral organs. Activity of the parasympathetic neurons in the dorsal motor nucleus of the vagus (DMV) determines the vagal tone and thereby modulates the function of the subdiaphragmatic organs. Leptin is highly involved in the regulation of food intake and alters neuronal excitability of brainstem neurons. Transient receptor potential vanilloid type 1 (TRPV1) has also been shown to increase neurotransmission in the brainstem and we tested the hypothesis that TRPV1 regulates presynaptic neurotransmitter release to leptin receptor‐expressing (LepRbEGFP) DMV neurons. Whole‐cell patch‐clamp recordings were performed to determine the effect of TRPV1 activation on excitatory and inhibitory postsynaptic currents (EPSC, IPSC) of LepRbEGFP neurons in the DMV. Capsaicin, a TRPV1 agonist increased the frequency of miniature EPSCs in 50% of LepRbEGFP neurons without altering the frequency of miniature IPSCs in the DMV. Stomach‐projecting LepRbEGFP neurons were identified in the DMV using the transsynaptic retrograde viral tracer PRV‐614. Activation of TRPV1 increased the frequency of mEPSC in ~50% of stomach‐related LepRbEGFP DMV neurons. These data demonstrate that TRPV1 increases excitatory neurotransmission to a subpopulation of LepRbEGFP DMV neurons via presynaptic mechanisms and suggest a potential interaction between TRPV1 and leptin signaling in the DMV.